Pursuing manufacturing-based export-led growth: Are developing countries increasingly crowding each other out? - Arslan Razmi (University of Massachusetts, Department of Economics, 2006)
This study empirically investigates the presence of crowding out effects emerging from intra-developing country competition in export markets for manufactured goods. Export equations are estimated for a panel consisting of twenty major developing country exporters of manufactures, after developing weighted price and quantity indexes based on their exports to thirteen major industrialized countries. The results indicate that in spite of an increase in the elasticity of industrialized country expenditures on imported products, crowding out effects became much more significant in the 1990s. The estimated crowding out effects vary across time periods, SITC categories, and levels of technological sophistication of exports.
Keywords: 330; crowding out; export displacement; real exchange rates; intra-developing country competition; dynamic panel data techniques; generalized method of moments; Exportinduziertes Wachstum; Crowding out; Internationaler Wettbewerb; Momentenmethode; Entwicklungsländer